Critical Factors Hindering the Millet Entrepreneurial Sector: Strategic Interventions for Enterprise Development - Gudla, Manichandana; Rashmi Singh,; Manjeet Singh Nain,; Rabindra Nath Padaria,; K V Praveen,; Saurabh Tiwari,; Rajat Kumar Nath,; Sk Wasaful Quader,; Apoorva Veldandi, (Indian Journal of Extension Education, 2025)
The study was conducted to develop strategies in the context of the entrepreneurial climate of the millet-based enterprises on the basis of identified constraints faced by millet entrepreneurs and in the state of Telangana. The data were collected using a structured interview schedule from 35 millet entrepreneurs, 150 millet growers and 30 research scientists comprising 215 respondents from Telangana during the 2023-24. The constraints and strategies were divided into four categories, i.e., technical, financial, marketing and personal. The major constraints revealed were a lack of millet processing, non-remunerative prices for the produce, farmers getting minimal shares and significant stress due to uncertain returns, respectively. The strategies using analytical hierarchical process like setting up processing centres, advocating subsidies on the purchase of machinery and raw materials, integrating millets into government programmes and recognising and rewarding resilient millet entrepreneurs, respectively emerged. The study identified unique scenarios indicating the valuable perspectives of all stakeholders included in the study.